The case of the perfect dog - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2012)
"When a strange twist of events brings a yellow Labrador onto the scene of a roundup gone wrong, the entire ranch quickly falls in love with this newest addition to the ranch's Security Division. Who can help loving a Lab? Hank quickly begins to feel the pressure of measuring up to this perfect dog, but it isn't long before everyone begins to notice that their sweet new pet, Happy, has a few personality quirks of his own. Will Happy stay on the ranch forever? Will Hank manage to solve the crisis that erupts when Happy's quirks get out of hand, before Happy eats the ranch into bankruptcy?"-- P. [4] of cover.